MAC OS X Snow Leopard Server for dummies - Rizzo, John (--For dummies., 2010)
"Like everything Mac, Snow Leopard Server was designed to be easy to set up and use. Still, there are so many options and features that this book will save you heaps of time and effort. It walks you through installation, set-up on a virtual machine, directory services, managing clients, security, and everything necessary to keep your users happy"--Resource description page.